Evolution and Modernization of Islamic Education in Minangkabau - Alfurqan Alfurqan (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2020)
Surau is an Islamic education institution that is the prototype of other Islamic educational institutions in Minangkabau. Historically, the existence of surau began to decline due to modernization which permeated the Islamic world. The evolution of the Islamic education system from halaqah to classical, changes in curriculum, levels in the world of education, mixing of Islamic education with basic colonial lessons and so on are the effects of modernization and the development of the technology industry in the early 20th century and the millennial era today. The evolution of Islamic education in Minangkabau is caused by several factors, including the modernization of ideology and the influence of culture from other regions, the developing system of government, and the rapid advances in industrial technology. The method used is library research with historical and philological approaches.